Sodium bentonite and monensin under chronic aflatoxicosis in broiler chickens - Magnoli, Alejandra Paola (2011)
Clay feed additives have been increasingly incorporated into animal diets to prevent aflatoxicosis. Due to the nonselective nature of the binding interaction, many important components of the diets could also be made unavailable because of these feed additives. The anticoccidial monensin (MON) could also be sequestered by these clays. The use of sodium bentonite (Na-B) from a mine in the province of Mendoza, Argentina, was investigated as a sequestering agent to prevent the effects of 100 μg/kg of dietary aflatoxin B1 (AFB1). In vitro studies demonstrated that the above Na-B was a good candidate to prevent aflatoxicosis. They also showed that MON competes with AFB1 for the adsorption sites on the clay surface and effectively displaces the toxin when it is in low concentration. Even though the levels of MON in diets, approximately 55 mg/kg, are high enough to not be significantly changed as a consequence of the adsorption, they can further affect the ability of the clays to bind low levels of AFB1. An in vivo experiment carried out with poultry showed that 100 μg/kg of AFB1 does not significantly change productive or biochemical parameters. However, liver histopathology not only confirmed the ability of this particular Na-B to prevent aflatoxicosis but also the decrease of this capacity in the presence of 55 mg/kg of MON. This is the first report stressing this fact and further research should be performed to check if this behavior is a characteristic of the assayed Na-B or of this type of clay. On the other hand, the presence of MON should also be taken into account when assaying the potential AFB1 binding ability of a given bentonite.